Edukasi Masyarakat tentang Pentingnya Legalitas Usaha sebagai Penunjang Branding Produk - Syukur, Agus; Puspita, Ratna; Aulia, Nisrina Zahra; Diwani, Meftyane Liz; Bilqis, Shanaz Hafizah; Fitri, Qurrota A’yun Khoiriyyah (Journal of Community Service and Society Empowerment, 2025)
This community service activity aims to improve the knowledge and skills of MSME actors in understanding "The Importance of the Benefits of Business Legality as a Support for Product Branding" Legality has an important role as a support for product branding because it provides credibility, trust, and protection for products. With benefits, increasing consumer trust, increasing competitiveness, protecting product rights, facilitating collaboration and improving brand reputation. Participants in this community service activity from the Indonesian Hands Foundation (GTI) will be equipped with an understanding of the importance of business legality. With training, MSME actors are expected to be able to understand business legality in order to compete effectively and optimally as a support for product branding, so that they can increase the reach and competitiveness of sustainable businesses in the digitalization era.